2022
DOI: 10.4041/kjod21.126
|View full text |Cite
|
Sign up to set email alerts
|

Validation of three-dimensional digital model superimpositions based on palatal structures in patients with maximum anterior tooth retraction following premolar extraction

Abstract: Objective: This study aimed to evaluate the superimposition accuracy of digital modes for measuring tooth movement in patients requiring anterior retraction after premolar extraction based on the proposed reference regions. Methods: Forty patients treated with bilateral maxillary first premolar extraction were divided into two groups: moderate retraction (< 7.0 mm) and maximum retraction (≥ 7.0 mm). Central incisor displacement was measured using cephalometric superimpositions and three-dimensional (3D) digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, although the literature is vast in works that used reference points and regions in the maxilla, they differ regarding which region presents more stability, and none had been designated as gold standard. 15 …”
Section: Maxillary Model Superimpositionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, although the literature is vast in works that used reference points and regions in the maxilla, they differ regarding which region presents more stability, and none had been designated as gold standard. 15 …”
Section: Maxillary Model Superimpositionmentioning
confidence: 99%
“… 7 Some studies suggested concomitant palatal rugae alterations in the anterior and lateral end area following tooth movement, especially in patients who underwent tooth extraction. 15 , 16 …”
Section: Maxillary Model Superimpositionmentioning
confidence: 99%
See 3 more Smart Citations